Impact of antibiotics, iron oxide, and sodium sulfate on microbial community composition in laboratory-built municipal solid waste microcosms. - Judy Malas; Sarah C Khoury; Michael Tanzillo; Gracie A Fischer; Jean E Bogner; D'Arcy R Meyer-Dombard (PLoS ONE)
Municipal solid waste (MSW) landfills represent underexplored microbial ecosystems. Landfills contain variable amounts of antibiotic and construction and demolition (C&D) wastes, which have the potential to alter microbial metabolism due to biocidal or redox active components, and these effects are largely underexplored. To circumvent the challenge of MSW heterogeneity, we conducted a 65-day time series study on simulated MSW microcosms to assess microbiome changes using 16S rRNA sequencing in response to 1) Fe(OH)3 and 2) Na2SO4 to represent redox active components of C&D waste as well as 3) antibiotics. The addition of Fe(OH)3 altered the overall community composition and increased Shannon diversity and Chao1 richness. The addition of a mixture of seven antibiotics (1000 ng/L each) altered the community composition without affecting diversity metrics. Sulfate addition had little effect on microbial community composition or diversity. These results suggest that the microbial community composition in fresh MSW may be significantly impacted by influxes of iron waste and a single application of antibiotics.